PERENCANAAN SHOULDER PILE PENAHAN LONGSORAN DI LOKASI A1-P1 JEMBATAN PENGGARON (STUDI KASUS PROYEK PEMELIHARAAN JEMBATAN PENGGARON TAHUN 2019-2020) - Kholik, Idham (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
A bridge is one of the constructions that functions to connect two parts of the road that were cut off due to obstacles such as deep valleys, rivers, railroads, roads that cross not a level and others. So in the construction of a bridge, calculations and attention to other aspects such as nature and the surrounding environment are needed which can affect the stability of the bridge itself. One of the things that can disturb the balance of the bridge is landslides. Handling of landslide hazards is also carried out at the Penggaron bridge which is located on the Trans Jawajalur Semarang - Solo toll road Km 427 + 400 - 427 + 800 with a length of 400, one of which is by making a Shoulder Pile to withstand landslides as well as analyzing the environmental impacts (natural consequences) that occur by looking at and analyzing data from the bore log.Keywords: Bridge, Toll Road, Shoulder Pile, Landslide